2020
DOI: 10.3390/tropicalmed5030111
|View full text |Cite
|
Sign up to set email alerts
|

Cholera and Pancreatic Cholera: Is VIP the Common Pathophysiologic Factor?

Abstract: Background: Cholera remains a major global health problem, causing high output diarrhea leading to severe dehydration and shock in developing countries. We aimed to determine whether vasoactive intestinal polypeptide (VIP), the mediator of pancreatic cholera syndrome, has a role in the pathophysiology of human cholera. Methods: We conducted a prospective observational study of cholera cases hospitalized with severe dehydration. Plasma and stool water levels of VIP were measured just after admission, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…29–30) agreed with Jaehnichen and others that cholera was an affliction of the symphatique or “pneumo-gastrique nerve”. Here again is an ironic and seemingly prescient but totally unrelated idea which in modern times has emerged as a role for the nervous system and gut hormones in choleragenesis [ 25 ]. The chance use of seemingly prescient but actually unrelated descriptive phrases often suggests ideas that the authors could not have understood as we do today.…”
Section: Rudolf Hermann and Friedrich Jaehnichenmentioning
confidence: 99%
“…29–30) agreed with Jaehnichen and others that cholera was an affliction of the symphatique or “pneumo-gastrique nerve”. Here again is an ironic and seemingly prescient but totally unrelated idea which in modern times has emerged as a role for the nervous system and gut hormones in choleragenesis [ 25 ]. The chance use of seemingly prescient but actually unrelated descriptive phrases often suggests ideas that the authors could not have understood as we do today.…”
Section: Rudolf Hermann and Friedrich Jaehnichenmentioning
confidence: 99%
“…A prospective study on 23 cholera patients found vasoactive intestinal polypeptide (VIP) normal in plasma (≤30 pmol/L), but very high in stool water (mean 208 pmol/L), the latter significantly associated with duration of hospitalization and stool volume ( P < 0.05). The authors discuss a theoretical approach by locally modulating VIP in cholera [2 ▪ ].…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…No mass screening of compounds likely to have such efficacy has been undertaken despite an abundance of potential candidates. Recent advances in cholera pathophysiology, such as confirmation of the role of VIP in human cholera [ 4 ], suggest a number of potential high-value targets which merit inclusion in such a screening program in animal models leading to clinical trials.…”
mentioning
confidence: 99%